Transversus Abdominis Plane Blocks in Microsurgical Breast Reconstruction: A Systematic Review and Meta-analysis - Abdou, Salma A.; Daar, David A.; Wilson, Stelios C.; Thanik, Vishal (Journal of Reconstructive Microsurgery, 2020)
Background Transversus abdominis plane (TAP) blocks have been shown to significantly reduce pain and narcotic consumption following major abdominal surgeries. This study investigates the literature on their use in microsurgical breast reconstruction.Patients and Methods A systematic review of TAP blocks in autologous breast reconstruction was performed.Results Across 10 included studies, 174 patients (5 studies) received an intraoperative TAP block injection, 185 patients (4 studies) received a TAP catheter for intermittent postoperative analgesia, and 325 patients served as controls for a total of 684 included patients. The majority of TAP block delivery techniques were ultrasound guided (7/10 studies). Liposomal bupivacaine (LB) was the most commonly used analgesic (4 studies and139 patients) followed by conventional bupivacaine (3 studies and 105 patients). Eight studies found a significant reduction in oral, intravenous, and/or total morphine requirements in the TAP group when either the daily average and/or total inpatient consumption was compared with the control. Hospital length of stay was significantly shorter for patients undergoing single intraoperative TAP block injection with any analgesic as compared with standard narcotic-based protocols (mean difference= −0.95 days; 95% CI: −1.72 to −0.17 days; p = 0.02). Looking at TAP blocks specifically with LB, there was a mean decrease of 0.83 days as compared with the control, which was not statistically significant (95% CI: −1.90 to 0.25 days; p = 0.13).Conclusion While the current data support the use of TAP blocks in autologous breast reconstruction, additional studies with more standardized protocols should be performed to determine the most optimal practice.
Keywords: Transversus abdominis plane block; liposomal bupivacaine; deep inferior epigastric perforator flap; autologous breast reconstruction; postoperative management; opioid consumption